(5t-3)=3(t+1)+3

Simple and best practice solution for (5t-3)=3(t+1)+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5t-3)=3(t+1)+3 equation:


Simplifying
(5t + -3) = 3(t + 1) + 3

Reorder the terms:
(-3 + 5t) = 3(t + 1) + 3

Remove parenthesis around (-3 + 5t)
-3 + 5t = 3(t + 1) + 3

Reorder the terms:
-3 + 5t = 3(1 + t) + 3
-3 + 5t = (1 * 3 + t * 3) + 3
-3 + 5t = (3 + 3t) + 3

Reorder the terms:
-3 + 5t = 3 + 3 + 3t

Combine like terms: 3 + 3 = 6
-3 + 5t = 6 + 3t

Solving
-3 + 5t = 6 + 3t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-3t' to each side of the equation.
-3 + 5t + -3t = 6 + 3t + -3t

Combine like terms: 5t + -3t = 2t
-3 + 2t = 6 + 3t + -3t

Combine like terms: 3t + -3t = 0
-3 + 2t = 6 + 0
-3 + 2t = 6

Add '3' to each side of the equation.
-3 + 3 + 2t = 6 + 3

Combine like terms: -3 + 3 = 0
0 + 2t = 6 + 3
2t = 6 + 3

Combine like terms: 6 + 3 = 9
2t = 9

Divide each side by '2'.
t = 4.5

Simplifying
t = 4.5

See similar equations:

| 3ab^2+6a= | | 7(r)=3.14r^2 | | 3x^2+8=-56 | | -11x+2(3x-5)=-17-4x | | 6(z+8)=5(z-4)+z | | 4cosx-7sinx=0 | | 6(z+8)=6(z-4)+z | | 7n+10=2.5 | | 3x^4+6y^2+6= | | n-44=0 | | 2(20)+9y=1800 | | 5x^3-15x^2-x+3= | | 4(30)+6y=2400 | | 0.09x+x=21800 | | 0.3m+1-1.6m=5 | | 3x+24+58=x+41 | | 3.75m+1-1.6m=5 | | 3x+24+58= | | 3.76m+1-1.6m=5 | | 58+3x+24=x+41 | | 36x=26x | | 58+3x=17 | | 28y+7x=56 | | 7x+28y=56 | | 9x+17=-7 | | 8x+750=30x-650 | | C^2-4c= | | 4z=5z-18 | | 2a+3b=83 | | 2p^3q^2+p^2q+pq= | | 8(v+2)-4v=2(2v+1)-11 | | -3m=j-18 |

Equations solver categories